Short-Term and Long-Term Outcomes of Kidney Transplantation in Diabetic and Nondiabetic Patients - Shahbazian, Heshmatollah; Shahbazian, Hajieh (Urology Journal, 2009)
Introduction: The purpose of this study was to compare the short-term and long-term kidney transplant outcomes in diabetic and nondiabetic patients. Materials and Methods: We studied all kidney recipients in Golestan hospital, Ahwaz, from 1995 to 2003. The patients were divided into two groups of diabetic and nondiabetic, and 1-year, 2-year, and 5-year survival rates of the patient and the kidney were evaluated. We also evaluated and compared the causes of death between these two groups. Results: There were 50 diabetic patients with a mean age of 51 years, and 350 nondiabetic patients with the mean age of 29 years old (P = .03). One-year, 2-year, and 5-year graft survival rates were 90% versus 91.5%, 86% versus 89%, and 76% versus 83% in diabetic and nondiabetic patients, respectively (P = .19). The patient survival rates were 92% versus 93%, 88% versus 91%, and 76% versus 84% in diabetic and nondiabetic patients, respectively. The most common cause of death was myocardial infarction in diabetic patients (50%), and septicemia among the nondiabetic ones (50%). The most common cause of kidney allograft loss was patient’s death (75%) in diabetic patients and kidney rejection (40%) in nondiabetics. Conclusion: Long-term kidney transplantation results have been significantly improved comparing with other studies. Thus, kidney transplantation is recommended as theÂ treatment of choice in diabetic patients with end-stage renal disease. However, a complete evaluation of cardiac problems for these patients is recommended before the surgery.